Papillary and ductal patterns of mesonephric-like adenocarcinomas are often overlooked: a retrospective revaluation of over 1000 endometrial carcinomas - Akbari, Ardalan; Pors, Jennifer; Lum, Amy; Leung, Samuel; Cochrane, Dawn; Jamieson, Amy; Mcalpine, Jessica; Kommoss, Stefan; Huvila, Jutta; Huntsman, David; Talhouk, Aline; Singh, Naveena; et al. (WILEY, 2025)
Aims Mesonephric-like adenocarcinoma (MLA) of the endometrium is often a diagnostic challenge, due to its morphological resemblance to other more common M & uuml;llerian neoplasms. This study aimed to retrospectively identify overlooked MLA in a large endometrial carcinoma cohort, using a combination of immunohistochemistry (IHC), morphology and KRAS sequencing.
Methods and results IHC was conducted on 1094 endometrial carcinomas, identifying 16 potential MLA cases based on GATA3+ and/or TTF1+ and ER- staining patterns, which subsequently underwent detailed histological review, KRAS sequencing and ProMisE molecular classification. Of the IHC screen-positive cases, one was positive for both GATA3 and TTF1, nine were positive for GATA3 only and six were positive for TTF1 only. All IHC screen-positive cases were POLE wild-type. All five tumours in the NSMP category showed morphological features of MLA, while the three MMRd and eight p53abn tumours did not show MLA morphology. The five cases diagnosed as MLA on review were all originally diagnosed as low-grade endometrioid adenocarcinoma probably because of rare morphological patterns, being predominantly papillary or ductal. Four of the five cases harboured a KRAS mutation
Conclusion This study highlights the importance of a comprehensive diagnostic approach for accurately identifying endometrial MLA and for pathologists to be aware of papillary and ductal patterns in endometrial carcinoma assessment. Further exploration into the molecular landscape of MLA is essential for refining diagnostic criteria and developing targeted therapies.